Efficient liquid metallurgy synthesis of Fe–TiB2 high modulus steels via in-situ reduction of titanium oxides. (5th May 2016) - Baron, C.; Springer, H.; Raabe, D.
Abstract: We studied the in-situ reduction of Ti oxides by Al as an alternative and cost effective route for the liquid metallurgical synthesis of low density, high stiffness steels (high modulus steels) containing about 10 vol.% TiB2 . TiO2, TiO1.83 and TiO were inserted via iron tubes into Fe–B melts, with Al either premixed with the oxide powders or liquid in the melt. Depending on Ti oxide type and location of the redox partner Al, greatly differing reaction kinetics, slag formation and corresponding microstructures of the high modulus steels were observed. TiO1.83 and TiO premixed with Al showed the highest TiB2 yield in the cast steel and are thus favourable candidates for the cost effective production of high modulus steels. Based on our findings, a novel synthesis process is proposed, based on filling wire injection into a continuous casting process, allowing the utilisation of the additionally formed oxide particles for the further improvement of the property profile of high modulus steels. Graphical abstract: Highlights: Liquid metallurgy production of steels with high stiffness and low density Utilisation of aluminothermic reduction for high cost efficiency TiO1.83 and TiO premixed with Al show the highest TiB2 yield. Novel synthesis route proposed to utilise oxide particles.